Analisis Perbandingan Risk & Return Pembiayaan Antar BPRS di Yogyakarta dengan Metode RAROC - Wulan Mufitasari (FAI, 2017)
Analisis Perbandingan Risk & Return Pembiayaan Antar BPRS di Yogyakarta dengan Metode RAROC